Ice stream dynamics inferred from seismic geomorphology from the Bjørnøyrenna and Nordkappbanken area, SW Barents Sea - Khan, Mohammad Ibrahim (Universitetet i Tromsø, 2013)
The aim of this master thesis is to investigate ice streams dynamics in Bjørnøyrenna and Nordkappbanken areas in south-west Barents Sea shelf Ice streams are responsible for the drainage of majority of ice from ice sheet and play a key role in the dynamic nature and stability of ice sheets, based mainly on six 3D seismic data sets,. Regional 2D lines are also used to establish the regional stratigraphy and for correlation purposes. A total of 15 horizons were interpreted in the various cubes. On all the sub-surface horizons, depressions and megascale glacial lineations (MSGLs) were observed, the latter being indicative of fast flowing paleo-ice streams. Most of these surfaces exhibit multiple generations of MSGLs indicating changes in ice stream source areas or flow of different ice streams. The paleo-ice streams on the seafloor are attributed to deglaciation of the Barents Sea while some of the subsurface paleo-ice streams may have formed during the Last Glacial Maximum (LGM). Glaciotectonic origin is inferred for most of the depressions with some being additionally attributed to fluid flow expulsion. Channels are inferred to be formed from glacial melt-water.